Death domain fold proteins in immune signaling and transcriptional regulation. (13th May 2021) - Huoh, Yu‐San; Hur, Sun
Abstract : Death domain fold (DDF) superfamily comprises of the death domain (DD), death effector domain (DED), caspase activation recruitment domain (CARD), and pyrin domain (PYD). By utilizing a conserved mode of interaction involving six distinct surfaces, a DDF serves as a building block that can densely pack into homomultimers or filaments. Studies of immune signaling components have revealed that DDF‐mediated filament formation plays a central role in mediating signal transduction and amplification. The unique ability of DDFs to self‐oligomerize upon external signals and induce oligomerization of partner molecules underlies key processes in many innate immune signaling pathways, as exemplified by RIG‐I‐like receptor signalosome and inflammasome assembly. Recent studies showed that DDFs are not only limited to immune signaling pathways, but also are involved with transcriptional regulation and other biological processes. Considering that DDF annotation still remains a challenge, the current list of DDFs and their functions may represent just the tip of the iceberg within the full spectrum of DDF biology. In this review, we discuss recent advances in our understanding of DDF functions, structures, and assembly architectures with a focus on CARD‐ and PYD‐containing proteins. We also discuss areas of future research and the potential relationship of DDFs with biomolecular condensates formed by liquid–liquid phase separation (LLPS). Abstract : The death domain fold (DDF) is a protein interaction motif that has the unique ability to densely pack into homomultimers or filaments. DDF‐mediated filament formation plays a central role in mediating immune signaling pathways and transcriptional regulation. In this review, we discuss recent advances in our understanding of DDF functions, structures, and assembly architectures. We also consider areas of future research and the potential relationship of DDFs with biomolecular condensates. ​